Commentary: Gender diversity and adolescent mental health – a reflection on Potter et al. (2020). (31st August 2020) - Burke, Sarah M.
Abstract : Using a multidimensional measure of gender identity for youths, Potter and colleagues elegantly investigated the prevalence of gender diversity and associated mental health problems in a large sample of young adolescents. The authors address an important need of studies within the behavioral and medical sciences to consider more carefully variations in a person's subjective experience of gender. Their study shows that individual differences in gender identity significantly relate to adolescent mental health problems. Moreover, findings of the current study, and future follow‐up assessments of the ABCD cohort, will, hopefully, add important quantitative, empirical data to the controversial discussions on gender identity development and gender diversity in childhood and adolescence ( Journal of Child Psychology and Psychiatry, 59, 2018, 1244; Pediatric gender identity, 2020, Cham, Switzerland: Springer International; International Journal of Transgenderism, 19, 2018, 225).